Firm Acquisitions and Technology Strategy: Corporate versus Private Equity Investors - Katrin Hussinger; Christoph Grimpe (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
Over the last few years, worldwide mergers and acquisitions (M&A) have increased sharply both in terms of value and volume. This development has not only been driven by corporate acquirers but also to an increasing extent by private equity investors. In this paper, we analyze differences in acquisition motives for corporate and private equity investors. We pay particular attention to the importance of technological assets in M&A transactions and distinguish between the technological value of patents and their potential to block competitors in technology markets. Our empirical results for European firm acquisitions in the period from 1999 to 2003 show that both corporate and private equity investors pay a higher price for target firms with valuable patents. However, patents with a potential to block technology competitors seem to be only of interest to corporate investors, especially if these are closely related to the patent portfolio of the acquirer.
Keywords: G34; L20; O34; 330; M&A; technology; patents; corporate and private equity investors; Übernahme; Private Equity; Wettbewerbsstrategie; Vergleich; Technologie; Patent; Europa